PELAKSANAAN KEGIATAN EKSTRAKURIKULER DALAM RANGKA PENGEMBANGAN NILAI-NILAI KARAKTER SISWA UNTUK MENJADI WARGA NEGARA YANG BAIK DI SMA KORPRI BANJARMASIN - Noor Yanti, Rabiatul Adawiah, Harpani Matnuh (Prodi PPKn ULM dan AP3KnI Kal-Sel, 2016)
Extracurricular activities are educational activities outside of school hours devoted to helping the development of learners, according to the needs, potential, talents, and interests through activities that are specifically organized by learners and educators capable and berkewenangan in SMA KORPRI Banjarmasin. This activity is conducted to develop character values KORPRI high school students in Banjarmasin. This study aims to investigate the implementation of extracurricular activities in high school KORPRI Banjarmasin, motivation of students in extracurricular activities in high school KORPRI Banjarmasin, as well as the character values that develop students in extracurricular activities in high school KORPRI Banjarmasin.The method used in this study is qualitative data collection techniques using observation, interviews and documentation. Data analysis was done by summarizing, presenting the data and draw conclusions.The results of this study indicate that: (1) the extracurricular activities were carried out in high school KORPRI Banjarmasin namely futsal, basketball, dance, dance, scouts, paskibra, martial arts, japan club, PMR (youth red cross), Habsy and volleyball (2) motivation of students in the implementation of extracurricular activities in high school KORPRI Banjarmasin still lacking, it is evident from the number of students who take the extracurricular activities are few and (3) Values of characters developed in extracurricular activities in high school KORPRI Banjarmasin is hard work, discipline, responsibility, relegius, democratic, curiosity, friends / communicative, patriotism, honesty, tolerance, the spirit of nationalism, peace-loving, creative, environmental care, social care, appreciate the achievements, like reading and independent.Based on these results, it is suggested that more teachers to motivate students to participate in extracurricular activities so that the development of character values can be more effective Keywords: Extracurricular Activities, Values Character.